TAKING CARE OF EARNINGS MANAGEMENT: DETECTION USING INTERNAL CONTROL REVIEW AND FINANCIAL RATIO ANALYSIS - Siti Hajarunnisya , Desi Adhariani (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This study aimed to analyse the role of internal control and financial ratio analysis on preventing and detecting earnings management in the financial statement of companies listed on the Indonesia Stock Exchange. This study uses a quantitative research approach with a panel data regression model. The calculation of earnings management was conducted based on the model developed by Kothari et al. (2005). Using 628 sample companies for the period of 2015- 2016, the results show that effective internal control could reduce the tendency of earnings management and that financial ratios could significantly provide indication of irregularities in financial statements.